Development and Rasch Validation of An Emotional Intelligence Scale for Secondary School Students - Indi Siti Nurihsani; Mubiar Agustin; Idat Muqodas (Journal of Educational Sciences, 2026)
This study aims to develop and validate an emotional intelligence scale for secondary school students to support comprehensive assessment beyond cognitive achievement. Emotional intelligence is essential for students’ ability to regulate emotions, maintain motivation, and establish positive social relationships, which contribute to academic success and well-being. This research employed a quantitative approach using the Rasch measurement model to evaluate the instrument’s psychometric properties. The instrument consisted of 30 items representing five dimensions: self-awareness, self-regulation, self-motivation, empathy, and social skills, and was administered to 75 students. The results showed high item reliability (0.98) and acceptable person reliability (0.75), with a strong item separation index of 7.08. Most items fit the Rasch model, although a few items indicated misfit and require refinement. The rating scale functioned effectively, and the instrument successfully differentiated students’ emotional intelligence levels. In conclusion, the developed scale is a valid and reliable tool for assessing emotional intelligence and can support educational interventions aimed at enhancing students’ holistic development.